Docetaxel versus active symptom control for refractory oesophagogastric adenocarcinoma (COUGAR-02): an open-label, phase 3 randomised controlled trial - Ford, Hugo; Marshall, Andrea; Bridgewater, John A.; Janowitz, Tobias; Coxon, Fareeda; Wadsley, Jonathan; Mansoor, Wasat; Fyfe, David; Madhusudan, Srinivasan; Middleton, Gary; Swinson, Daniel; Falk, Stephen; et al. (Elsevier, 2014)
BACKGROUND: Second-line chemotherapy for patients with oesophagogastric adenocarcinoma refractory to platinum and fluoropyrimidines has not shown benefits in health-related quality of life (HRQoL). We assessed whether the addition of docetaxel to active symptom control alone can improve survival and HRQoL for patients.